Comparison of two different IV anaesthetic agents during rigid bronchoscopy [Rijid bronkoskopi uygulamasinda iki farkli IV anestezik ajanin karsilastirilmasi] - (:unkn) unknown (My University, 1997)
This study was designed to compare the effects of two different anesthetic agents used during rigid bronchoscopy in pediatric patients. A total of 30 patients were divided into two groups. Anaesthesia was induced with thiopentone 5 mg/kg IV and propofol 3 mg/kg IV in the first and second groups respectively. All the patients received alfentanil in a dose of 10 μg/kg intravenously. Muscle relaxation was done with succinylcholine 1 mg/kg intravenously. Arterial blood pressure, heart rate, oxygen saturation of the patients were determined before and after anaesthesia induction, immediately after the placement of rigid bronchoscope, and at intervals of 2 minutes throughout the procedure. Patients were evaluated in regard to nausea, vomiting, coughing, laryngospasm, and bronchospasm immediately and 60 minutes after the cessation of the anaesthesia. Systolic arterial pressure, oxygen saturation were similar in both groups (p>0.05). Diastolic and mean arterial pressure noted after induction and at the 2nd minute of bronchoscopy were found to be significantly low in the propofol group (p<0.05). Heart rate measurements were also significantly low in the propofol group at the 4th, 6th, 8th and 10th minutes during bronchoscopy (p<0.05). Following awakening of the patients, coughing occured in 4 (26.66%), laryngospasm in 4 (26.66%), bronchospasm in 4 (26.66%) of the patients in thiopentone group. Of the patients in the propofol group; coughing occured in 5 (33.33%), laryngospasm in 2 (13.33%). There was no any complaint in both groups 60 minutes after bronchoscopy. There was no nausea and vomiting in both groups. In conclusion, hemodynamic parameters were less effected with propofol when compared to thiopentone during rigid bronchoscopy in pediatric patients and recovery after propofol was more comfortable.
Keywords: general anaesthesia; propofol; rigid bronchoscopy; thiopentone